Cilostazol in Pulmonary Fibrosis: A Molecular Docking Approach to Target Protein discovery - Misar, Pranaya; Otari, Kishor (Journal of Neonatal Surgery, 2025)
Pulmonary fibrosis (PF) is a chronic, progressive, and often fatal interstitial lung disease characterized by excessive extracellular matrix deposition, leading to irreversible lung damage and respiratory failure. Despite recent therapeutic advancements, effective treatments remain limited, highlighting an urgent need for novel pharmacological interventions. Cilostazol, a phosphodiesterase-3 (PDE3) inhibitor, exhibits diverse pharmacological properties, including anti-inflammatory, anti-platelet, and vasodilatory effects, and has shown promise in various fibrotic conditions. This study aimed to computationally identify potential target proteins of cilostazol relevant to the pathogenesis of pulmonary fibrosis using molecular docking simulations. A comprehensive library of known PF-related proteins was curated, and molecular docking was performed between cilostazol and these proteins using AutoDock Vina. Analysis of binding affinities and interaction patterns revealed several promising protein targets. We identify 5 potential therapeutic targets of cilostazol by molecular docking i.e., MMP7, TGF-β R1, Smad3, Wnt3a, GSK-3β and validate the results by evaluating its protective effect against pulmonary fibrosis. These findings suggest that cilostazol may exert its anti-fibrotic effects through multi-targeted mechanisms beyond its classical PDE3 inhibition, potentially modulating key signaling cascades involved in fibroblast activation, collagen synthesis, and inflammatory responses. This in silico investigation provides a foundational understanding of cilostazol's potential molecular targets in PF, paving the way for further in vitro and in vivo validation studies and its potential repurposing as a therapeutic agent for this devastating disease.